A Spatial and Temporal Comparative Analysis of the Effects of Land-Use Clusters on Activity Spaces in Three Quebec Cities. (December 2014) - Harding, Christopher; Patterson, Zachary; Miranda-Moreno, Luis F; Zahabi, Seyed Amir
Previous literature on transportation and land use has focused on the effect of individual land-use variables, such as population and employment density, and on measures of transportation demand, such as vehicle kilometers traveled and mode split. In contrast, our work uses activity spaces, a relatively unexplored measure of travel dispersal, as a dependent variable and neighborhood clusters to capture the effect of land use on this variable. This paper is an extension of previous research that dealt with Montreal exclusively and similar methods are used to compare three cities (Montreal, Quebec City, and Sherbrooke) over multiple years (1998–2008). We control and tests for the possibility of residential location self-selection bias through simultaneous equation modeling. The main findings are that (i) activity spaces are clearly linked to land use (through neighborhood clusters), as well as to overall city size; (ii) activity spaces appear to be growing over time where employment centers are fixed; and (iii) exogeneity in explanatory variables cannot be rejected.